Labrea-like hepatitis in Vitoria, Espirito Santo state, Brazil: report of a case - Pereira,Fausto Edmundo Lima (1993)
A case of fulminat hepatitis with microvesicular steatosis resembling Labrea 's fever, diagnosed in Vitoria (ES) is reported. The 16 year old bcy presented with severe epistaxis, agitation, jaundice and hemorrhagic vomiting and died two days after admission to the emergency unit of the Vnivesity Hospital. The disease started five days before with fever, myalgias, dark urine and jaundice andprogressed withpsychic agitation, torpor and coma. The liver andspleen were notpalpable. HBsAg was negative in the serum. The autopsy showed acute hepatitis with tylic necrosis confluent in the midizonal and periportal areas with massive microvesicular steatosis in the remaining hepatocytes. Mononuclear cellspredominated in the exudate. The reticulum showed condensation in the necrotic areas without typical bands of collapse. The portal tracts were edematous with mononuclear infiltration and mild bile duct proliferation. Absence of cholestasis. Exceptfor the confluent midzonalandperiportal necrosis this case showed several clinical and morphological aspects of the Labreafever describedfrom the East Amazon, demonstrating that the anatomical picture of this disease probabty is not in related to afactor peculiar to the Amazon region.